Prolonged Central μ-Opioid Receptor Occupancy after Single and Repeated Nalmefene Dosing - Ingman, Kimmo; Hagelberg, Nora; Aalto, Sargo; Någren, Kjell; Juhakoski, Auni; Karhuvaara, Sakari; Kallio, Antero; Oikonen, Vesa; Hietala, Jarmo; Scheinin, Harry (Neuropsychopharmacology (New York, N.Y.), 2005)
The opioid antagonist nalmefene offers an alternative to traditional pharmacological treatments for alcoholism. The present study was designed to investigate the relationship between nalmefene plasma concentration and central mu-opioid receptor occupancy after a clinically effective dose (20 mg, orally). Pharmacokinetics and mu-opioid receptor occupancy of nalmefene after single and repeated dosing over 7 days was studied in 12 healthy subjects. Serial blood samples were obtained after both dosings, and pharmacokinetic parameters for nalmefene and main metabolites were determined. Central mu-opioid receptor occupancy of nalmefene was measured with positron emission tomography (PET) and [(11)C]carfentanil at four time points (3, 26, 50, 74 h) after both dosings. Nalmefene was rapidly absorbed in all subjects. The mean t(1/2) of nalmefene was 13.4 h after single and repeated dosing. The accumulation of nalmefene and its main metabolites in plasma during the repeated dosing period was as expected for a drug with linear pharmacokinetics, and steady-state was reached for all analytes. Both nalmefene dosings resulted in a very high occupancy at mu-opioid receptors (87-100%), and the decline in the occupancy was similar after both dosings but clearly slower than the decline in the plasma concentration of nalmefene or metabolites. High nalmefene occupancy (83-100%) persisted at 26 h after the dosings. The prolonged mu-opioid receptor occupancy by nalmefene indicates slow dissociation of the drug from mu-opioid receptors. These results support the rational of administering nalmefene when needed before alcohol drinking, and they additionally suggest that a high mu-opioid receptor occupancy can be maintained when nalmefene is taken once daily.